2009
DOI: 10.1128/jcm.01321-08
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Human Clinical Isolates ofYersinia enterocoliticaBioserotype 1B/O8 in Poland: Emergence and Dissemination of Three Highly Related Clones

Abstract: Thirty-three clinical isolates of the highly pathogenic Yersinia enterocolitica bioserotype 1B/O8 were collected from sporadic cases in Poland from January 2004 to July 2008. The isolates carried major virulence markers and were strongly clonal. This is the first report of the emergence and dissemination of highly related clones of Y. enterocolitica 1B/O8 in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Biotype 1A isolates are considered nonpathogenic, which is concordant with a lack of the major Y. enterocolitica virulence factors such as pYV, invasin, YadA, and Ail (5), although there are numerous reports of biotype 1A human carriage (6,7). Biotype 1B isolates are high pathogenic, which is concordant with carriage of the high-pathogenicity island, but isolation from human disease cases is very rare with the exception of notable outbreaks such as the recent emergence in Poland (8). Biotype 2 to 4 isolates are low pathogenic and are globally the most common causes of human gastrointestinal yersiniosis (4).…”
mentioning
confidence: 97%
“…Biotype 1A isolates are considered nonpathogenic, which is concordant with a lack of the major Y. enterocolitica virulence factors such as pYV, invasin, YadA, and Ail (5), although there are numerous reports of biotype 1A human carriage (6,7). Biotype 1B isolates are high pathogenic, which is concordant with carriage of the high-pathogenicity island, but isolation from human disease cases is very rare with the exception of notable outbreaks such as the recent emergence in Poland (8). Biotype 2 to 4 isolates are low pathogenic and are globally the most common causes of human gastrointestinal yersiniosis (4).…”
mentioning
confidence: 97%
“…Biotype 1A is deemed to be non-or less pathogenic for humans. Biotype 1B is widespread in the United States and only rarely detected in Europe and Japan (11,14,26,28). Based on different DNA-DNA hybridization values and 16S rRNA gene sequences, it was proposed to name the "American" strains Y. enterocolitica subsp.…”
mentioning
confidence: 99%
“…In a previous study, we showed that clinical isolates of Y. enterocolitica 1B/O8 collected in Poland were clonal and belonged to the same strain sensu stricto [22]. This strong clonality of Polish Y. enterocolitica 1B/O :8 isolates may suggest a common origin.…”
mentioning
confidence: 85%